Microcarrier Screening for Skin-derived Precursor Schwann Cell Culture in Stirred Tank Bioreactors - Bowal, Kimberly; Walsh, Tylor; Midha, Rajiv; Kallos, Michael (CMBES Proceedings, 2016)
Skin derived precursor Schwann cells (SKP-SCs) are currently being investigated for use in peripheral nerve repair. Current static culture methods are not adequate to produce the high number of cells needed for treatments. As a result, suspension bioreactors are an attractive option. To culture adherent cells, like the SKP-SCs, in suspension, it is common practise to use small spherical beads called microcarriers. Microcarriers typically have diameters of 100µm to 400µm can be manufactured out of many materials, but are typically made from materials that can withstand the forces seen in a bioreactor. When inoculated, the cells will attach to the microcarriers and proliferate. This attachment depends on many factors including chemical composition, surface topography, degree of porosity, and charge. Because there are many different commercially available microcarriers with varying properties, we needed to screen these for our specific cell type. We selected four microcarriers to test, Cytodex 3, Hillex II, ProNectin F, and Plastic Plus. We first compared attachment to the microcarriers in shaken well plates, then compared the growth kinetics of SKP-SCs in the shaken well plates. Finally we investigated the growth kinetics of SKP-SCs in bioreactors. We found that Cytodex 3 and Hillex II had the highest attachment rate after 18 hours. Over the growth period of 9 days, Cytodex 3 showed significantly higher growth compared to the other microcarriers. Lastly Cytodex 3 had the highest growth in suspension bioreactors. Based on these results we are confident in using Cytodex 3 to develop our process further.